Further to the Opportunities to Elevate the Industrial Policy’ Effectiveness in the Arctic Zone of the Russian Federation - E. L. Moreva; L. V. Obolenskaya (Управленческие науки)
The actuality of the paper is due to the intensification of the strategic, geopolitical, economic, ecological and other challenges to the Russian Arctic’ industrial development which requires the State to respond to them. Thus, the improvement of the Industrial policy (IP) realized in the region and the determination of the opportunities to boost its effects are among the arctic agenda’ issues. The analysis and the assessment of the effectiveness of the course in practice form the objective of the present paper, with its tasks to define the opportunities to elevate the policy’ effectiveness. To solve the above problems, the authors used the general scientific research methods: analysis, synthesis, logical, dialectical, comparative and others. Their application to study the IP in the Arctic Zone of the Russian Federation (AZRF) resulted in the identification of a number of shortcomings when the policy’ development and implementation, i. e. the use of quantitative indicators of IP efficiency developed by the authors with the managerial factor accounted; the consideration of the continuity when changing the stages of strategic management; the compulsory use of the information support to the course as a special system that allows one to monitor constantly the effectiveness of IP and identify opportunities to improve it at the system level, as well as the recommendations to accomplish these possibilities.